Structural properties of zinc lithium borate glass - Saidu, Aminu (Maik Nauka-Interperiodica Publishing, 2014)
Zinc Lithium Borate glasses of different composition were prepared with the aim of using it for thermoluminescence dosimetry. Melt quenching method was adopted in this process. Fourier transform Infrared (FTIR) spectroscopy and UV-vis-NIR spectroscopy techniques were employed to investigate the infrared spectra and energy band gap of different composition of Zinc Lithium Borate glasses. X-ray diffraction analysis was used to confirm the amorphous nature of the glass samples. Glass forming ability and stability of the glass was checked using Differential thermal analysis (DTA). Density, molar volume, refractive index parameters have been analyzed in the light of different concentration of the modifier. The active vibrational modes of 1200–1600 cm−1 for B-O stretching of BO3 units, 800–1200 cm−1 for B-O stretching of BO4 units and 400–800 cm−1 for bending vibration of various borate segments were detected. Addition of ZnO to lithium borate shows its influence in converting the dominant BO3 group to BO4 group. BO4 are known for creating complex defects, a situation that established deep and stable traps good for thermoluminescence phenomena. From optical data, direct and indirect energy band gap has been calculated using the data obtained from UV-vis-NIR spectroscopy. Both direct and indirect band gaps decrease with the increase of modifier Li2CO3.